If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(z + 7) = 9 + 3z Reorder the terms: 5(7 + z) = 9 + 3z (7 * 5 + z * 5) = 9 + 3z (35 + 5z) = 9 + 3z Solving 35 + 5z = 9 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 35 + 5z + -3z = 9 + 3z + -3z Combine like terms: 5z + -3z = 2z 35 + 2z = 9 + 3z + -3z Combine like terms: 3z + -3z = 0 35 + 2z = 9 + 0 35 + 2z = 9 Add '-35' to each side of the equation. 35 + -35 + 2z = 9 + -35 Combine like terms: 35 + -35 = 0 0 + 2z = 9 + -35 2z = 9 + -35 Combine like terms: 9 + -35 = -26 2z = -26 Divide each side by '2'. z = -13 Simplifying z = -13
| 14=-1-5h | | 4a-5=3m+7 | | 2=3x+7 | | 7-8n+4n=16-97 | | -53+10y+4=4(4y-2)-5 | | 11=7-2k | | 7(c-2)+7=2+c-9 | | -10+4k=k-2k | | 5x-3y-15=0 | | 4n-8n=18 | | -10(x-3)+28=-16-16 | | 9y^3+2=y-18y | | 0=-6(y+9) | | 6.1-3x=4.2 | | a^2-3a-54= | | 1.0-6.4x=-9.4 | | r-11-8r=29 | | 2.4-8.6x=-26.5 | | (3x+1)-(x-1)=4 | | 11y-3=15 | | x^2+2xy-8y^2=0 | | 0.9-2.01-0.39x-0.6=0.44x-16.96+0.16x-0.74 | | (3x^2+6x-3)=0 | | (3x+1)-(x-1)=2 | | 6q-1=-q-8 | | t+(t+3)(-3)=t-3 | | p=-1.555555556 | | -4(4y-9)+2(2y+9)= | | 6y-9=13y+40 | | -275(-3x-5)=-5.75(1-2x) | | x^2-12x-180=0 | | d+6=6+d |